γ9δ2 T-Cell Expansion and Phenotypic Profile Are Reflected in the CDR3δ Repertoire of Healthy Adults - Vyborova, Anna; Janssen, Anke; Gatti, Lucrezia; Karaiskaki, Froso; Yonika, Austin; van Dooremalen, Sanne; Sanders, Jasper; Beringer, Dennis X.; Straetemans, Trudy; Sebestyen, Zsolt; Kuball, Jürgen (Frontiers in Immunology, 2022)
γ9δ2T cells fill a distinct niche in human immunity due to the unique physiology of the phosphoantigen-reactive γ9δ2TCR. Here, we highlight reproducible TCRδ complementarity-determining region 3 (CDR3δ) repertoire patterns associated with γ9δ2T cell proliferation and phenotype, thus providing evidence for the role of the CDR3δ in modulating in vivo T cell responses. Features that determine γ9δ2TCR binding affinity and reactivity to the phosphoantigen-induced ligand in vitro appear to similarly underpin in vivo clonotypic expansion and differentiation. Likewise, we identify a CDR3δ bias in the γ9δ2T cell natural killer receptor (NKR) landscape. While expression of the inhibitory receptor CD94/NKG2A is skewed towards cells bearing putative high-affinity TCRs, the activating receptor NKG2D is expressed independently of the phosphoantigen sensing determinants, suggesting a higher net NKR activating signal in T cells with TCRs of low affinity. This study establishes consistent repertoire-phenotype associations and justifies stratification for T cell phenotype in future research on γ9δ2TCR repertoire dynamics.